2015
DOI: 10.1038/ncb3175
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP1 opposes proliferative EGFR–SOS1–Ras signals and restricts intestinal epithelial cell growth

Abstract: The character of EGFR signals can influence cell fate but mechanistic insights into intestinal EGFR-Ras signalling are limited. Here we show that two distinct Ras nucleotide exchange factors, RasGRP1 and SOS1, lie downstream of EGFR but act in functional opposition. RasGRP1 is expressed in intestinal crypts where it restricts epithelial growth. High RasGRP1 expression in colorectal cancer (CRC) patient samples correlates with a better clinical outcome. Biochemically, we find that RasGRP1 creates a negative fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 69 publications
2
72
0
1
Order By: Relevance
“…Thus, we conclude that GPR182 normally functions to directly or indirectly inhibit MAPK-induced intestinal proliferation ( Figure 7D). This inhibitory function is consistent with the finding that GPR182 expression is significantly reduced in human colon adenocarcinoma -a novel finding that expands the growing cadre of negative regulators of proliferation, including LRIG1, that have been shown to be downregulated during colorectal tumorigenesis (20,(46)(47)(48)(49). Conversely, numerous pro-proliferative ISC markers, such as LGR5, BMI1, and SOX9, have all been shown to be upregulated in human colorectal carcinomas (50).…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, we conclude that GPR182 normally functions to directly or indirectly inhibit MAPK-induced intestinal proliferation ( Figure 7D). This inhibitory function is consistent with the finding that GPR182 expression is significantly reduced in human colon adenocarcinoma -a novel finding that expands the growing cadre of negative regulators of proliferation, including LRIG1, that have been shown to be downregulated during colorectal tumorigenesis (20,(46)(47)(48)(49). Conversely, numerous pro-proliferative ISC markers, such as LGR5, BMI1, and SOX9, have all been shown to be upregulated in human colorectal carcinomas (50).…”
Section: Methodssupporting
confidence: 75%
“…In addition, loss of the RTK negative regulator Lrig1 leads to constitutively active EGFR and other ERbB receptors, which lead to increased ERK1/2 signaling, hyperproliferation, and tumorigenesis (20,53). Oncogenic mutations in KRAS activate numerous downstream kinases, including ERK1/2, which rarely initiate tumorigenesis alone but, when combined with Apc inactivation, lead to increased adenoma formation and progression (48,(54)(55)(56)(57)(58). GPCRs can activate ERK1/2 directly through both G protein-and β-arrestin-mediated signaling, as well as indirectly through modulation of EGF/EGFR expression and/ or EGFR transactivation (59,60).…”
Section: Methodsmentioning
confidence: 99%
“…The CL1-5-F4 cells were generated from the CL1 human lung adenocarcinoma cells by five repeated in vitro selection processes of the invasive sublines generating the CL1-5 subline which was 6-fold more invasive than the parent cells22, then by four repeated in vivo selections of the highly invasive and migrative cells from the lungs of severe combined immunodeficient (SCID) mice generating the CL1-5-F4 subline23. Jurkat T-cell lymphoma cells are frequently used as EGFR-negative control cells in studies of various types of cancer212425.…”
Section: Resultsmentioning
confidence: 99%
“…Sos1 is the main mediator of Ras activation and is critical to cell proliferation through its activation of the Ras-GTP state and ERK phosphorylation. 24,25 Luciferase reporter assays showed that the mir-155 mimic reduced the activity of the reporter plasmid containing a 3 0 -UTR sequence of Sos1. We searched two mir-155 binding sites on Sos1 by TargetScan.…”
Section: Mir-155-containing Macrophage Exosomes Suppress Cardiac Fibrmentioning
confidence: 99%